Management Accounting as a Multi-Paradigm Discipline of Social Sciences - Masztalerz, Marek (Rachunkowość zarządcza jako wieloparadygmatyczna dyscyplina nauk społecznych, 2011)
This paper is a brief metatheoretical study of the management accounting thought. The purpose of this paper is to present management accounting as a multi-paradigm discipline of social science. The term "paradigm" is defined and briefly analyzed. The framework of Burrell and Morgan [1979] concerning paradigms in social science is described. Various approaches to the management accounting paradigms (in a broad and narrow senses) are presented and discussed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 87-96
Keywords: management accounting; paradigm; theory; research